Investigation of underground lignite coals washability in Turkey/Manisa- Soma -Karanlikdere location - Bilgin, Ömer; Kantarcı, Sadiye (My University, 2017)
The coal mining has been carried out coal mine since 150 years in the Turkey/Manisa-Soma. It has been determined that about 800 million tonnes of lignite reserves (ranging in calorific value from 2.500 to 4.500 kcal/ kg). Turkey/Manisa-Soma-Karanlikdere underground lignite coal is one of the highest reserves in Turkey and having about 5300 kcal of energy with quality and enrichment. Coal is contains very clay and abundant fossils. Limestone, sandstone and claystone are also frequently found. As the coal goes from the lower sections towards the upper sections, the coal calorie increases, the color turns black, the harder and vitrified structure gains, and at these levels there is a small amount of sulfur. In this study; coal samples were taken about 350-400 kg of the third shift at intervals of 45 minutes over the tape to the point where it spills into the band Soma-Karanlıkdere the underground coal mine pit-run state. The samples were carefully brought into the lab closed in sacks and bags. The samples were performed of the ash %, calories, moisture %, sulfur % analyzes. Then, the samples were subjected to sieve analysis of nine different particle size ranges. Later, lignite sieve analysis of the samples were conducted the original ash %, calory % and moisture % analyzes. The coal sample was subjected to the Float-Sink Test to determine the washability of the coal. ZnCl2 (zinc chloride) was used as heavy media material. The ash analysis was utilized to evaluate the float-sink tests.
Keywords: Coal; Float-Sink Test; Heavy Media Seperation; Washability